PSXI-32 Potential improvements in milk production of mid lactating Holstein cows through changes in the defoliation intensity on a mixed pasture. (5th December 2019) - Hinz, Oliver Fast; Chilibroste, Pablo; Menegazzi, Gabriel; Oborsky, Matías; Soca, Pablo; Genro, Cristina; Mattiauda, Diego A
Abstract: An experiment was performed to study the effect of two contrasting defoliation intensities of a fescue based pasture on milk production of 24 mid lactating multiparous cows. The animals were blocked according to parity, body weight (587 ± 42 kg), body condition score (2.77 ± 0.16) and calving date, and were randomly allocated to one of these two treatments: lax treatment (TL) 12 cm and control treatment (TC) 6 cm, with four replications. It was used a second-year pasture of Festuca arundinacea and Lotus corniculatus (2530 ± 180 kgDM/ha), divided into eight plots of 0.3 ha. Each plot was grazed by three cows during as many days as necessary until the defoliation height of each treatment was achieved. This would be determined by daily measures of the pasture height. Animals had one grazing session from 8:00 to 16:00 h. Both treatments received 7.5 kgDM of supplementation (17% Crude Protein; 2.81 Mcal/kgDM) in individual troughs. The cows were milked twice a day (05:00 and 17:00 h). Milk production was registered daily while milk composition was measured at the beginning and at the end of the experiment (samples from two consecutive milking). For milk yield results, a mixed model was used (Glimmix procedure, SAS 9.2, 2010) to analyse with treatment, day and their interaction as fixed effects and block as a random effect. While milk composition was analysed with only treatment as fixed effect. Milk yield was greater for TL than TC, while there was no difference in milk composition between treatments (Table 1). There is a significant effect of the day and an interaction between treatment and day (Figure 1), as difference was greater for TL to the end of the grazing period. This leads to the conclusion that it is possible to improve the milk production through less defoliation intensity.